Differentiating between benign follicular nodules and follicular neoplasms in thyroid liquid‐based cytology preparations. Issue 8 (2nd June 2016) - Suzuki, Ayana; Hirokawa, Mitsuyoshi; Higuchi, Miyoko; Takada, Nami; Yamao, Naoki; Kuma, Seiji; Miyauchi, Akira
Abstract : Background: The cytological morphology observed in liquid‐based cytology (LBC) preparations is dissimilar to that of conventional preparations. The aim of this report is to clarify the cytological differences between benign follicular nodules (BFNs) and follicular neoplasms (FNs) in LBC preparations and identify novel diagnostic criteria for LBC preparations. Methods: A retrospective review of LBC preparations from 38 BFN and 74 FN (57 follicular adenomas and 17 follicular carcinomas) cases confirmed by histological examination was conducted. LBC samples were obtained from the washout fluid in aspiration needles, fixed with CytoRich‐RED TM, and prepared using the SurePath TM method. Results: Fibrin was observed in 43.2% of FNs and in 23.7% of BFNs. The incidences of intercellular spaces, distinct outer margin, and cytoplasmic process were significantly higher in BFNs ( P < 0.01, P < 0.01, and P < 0.05, respectively). Elongated microfollicles were seen in 55.4% of FNs and 10.5% of BFNs ( P < 0.01). Membranous materials encircling the outer edge of the follicles were observed only in BFN cases (5.8%). There were no significant differences between follicular adenoma and carcinoma. Conclusion: Intercellular spaces, distinct outer margins of the follicular clusters, cytoplasmic process, and membranous materials constitute indicators of BFN in LBC preparations. Fibrin and elongated microfollicles point to FN. We believe that these findings will improve the diagnostic accuracy of thyroid LBC preparations. Diagn. Cytopathol. 2016;44:659–664. © 2016 Wiley Periodicals, Inc.